Penyuluhan Penyebab Kecacingan di Sekolah Dasar Balongga Kecamatan Dolo Selatan Kabupaten Sigi Provinsi Sulawesi Tengah - Slamet Ifandi; Andi Lindhemutianingrum Siradje (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Worm infestation caused by intestinal worms is a global health problem, including in Indonesia. Preschool and school children are the most vulnerable groups to infection. Although not fatal, worm infestation can lead to chronic infections and various health problems, such as low body weight, anemia, and decreased academic performance. Therefore, education on the causes of worm infestation using lectures and leaflets was conducted. The purpose of this activity was to educate participants about the causes of worm infestation and prevention methods as well as the importance of maintaining environmental cleanliness. The results of this activity showed an increase in participants' understanding of worm infestation, with an average score of 60.0% to 88.6%. This activity can also have an impact on reducing cases of worm infections.